Implementing Cloud Design Patterns for AWS : Solutions and Design Ideas for Solving System Design Problems, 2nd Edition. - Keery, Sean (Packt Publishing, Limited, 2019)
Implementing AWS Patterns provides reproducible processes, practices, and blueprints for delivering secure, extensible, cloud-native products. This guide will help you leverage AWS' extensive offerings to solve common problems with Amazon Web Services. It will equip you to easily develop solutions using repeatable designs.